Testing the Antioxidant Activity of Ethanol Extract on Terap Fruit Seeds (Artocarpus odoratissimus) using the DPPH Method: Uji Aktivitas Antioksidan Ekstrak Etanol Pada Biji Buah Terap (Artocarpus odoratissimus) Menggunakan Metode DPPH - Aisya Maulidia; Wijayanti, Sari; Mustamin, Faizal; Ubrusun, Jufri (Jurnal FARMASIMED (JFM), 2024)
Plants contain compounds that are classified as secondary metabolites. One of them is terap fruit (Artocarpus odoratissimus). Terap (Artocarpus odoratissimus) is a plant that grows a lot in Kalimantan. Most of the Artocarpus genus have pharmacological properties. One of the benefits of these compounds is as an antioxidant. Antioxidants can remove free radical compounds in the body and prevent the onset of disease. Secondary metabolite compounds found in plants have been isolated and used as components in medicine. The study was intended to determine the antioxidant activity of ethanol extract of terap fruit seeds (Artocarpus odoratissimus) using the DPPH method. The method in this study was quantitative experimental, which included collecting and collecting plants, making simplicia, making extracts from terap seeds (Artocarpus odoratissimus) using 96% ethanol solvent, and for antioxidant activity testing using the DPPH method. The presence of antioxidant compounds in plant extracts can cause a change in the color of DPPH from purple to yellow. This color change will indicate antioxidant activity against DPPH free radicals and is measured by UV-Vis Spectrophotometry. Antioxidant activity was measured using the IC50 value (50% Inhibitory Concentration). From the results of the antioxidant activity test using the DPPH method, it can be concluded that the ethanol extract of terap fruit seeds obtained from the Tarakan area showed antioxidant activity. The IC50 value of 197.45 mg/ml indicates that its antioxidant ability is impaired as a weak antioxidant.